Some geometric properties of magneto-fluid flows - S. S. Gangwar; Ram Babu (International Journal of Mathematics and Mathematical Sciences)
By employing an anholonomic description of the governing equations, certain geometric results are obtained for a class of non-dissipative magnetofluid flows. The stream lines are geodesics on a normal congruence of the surfaces which are the Maxwellian surfaces.